Genotyping and Antimicrobial Susceptibility Profiling of Streptococcus uberis Isolated from a Clinical Bovine Mastitis Outbreak in a Dairy Farm - Valentina Monistero; Antonio Barberio; Paola Cremonesi; Bianca Castiglioni; Stefano Morandi; Desiree C. K. Lassen; Lærke B. Astrup; Clara Locatelli; Renata Piccinini; M. Filippa Addis; Valerio Bronzo; Paolo Moroni (MDPI AG, 2021)
Streptococcus uberis, an environmental pathogen responsible also for contagious transmission, has been increasingly implicated in clinical mastitis (CM) cases in Europe. We described a 4-month epidemiological investigation of Strep. uberis CM cases in an Italian dairy farm. We determined molecular characteristics and phenotypic antimicrobial resistance of 71 Strep. uberis isolates from dairy cows with CM. Genotypic variability was investigated via multiplex PCR of housekeeping and virulence genes, and by RAPD-PCR typing. Antimicrobial susceptibility was assessed for 14 antimicrobials by MIC assay. All the isolates carried the 11 genes investigated. At 90% similarity, two distinct clusters, grouping 69 of the 71 isolates, were detected in the dendrogram derived from the primer ERIC1. The predominant cluster I could be separated into two subclusters, containing 38 and 14 isolates, respectively. Strep. uberis strains belonging to the same RAPD pattern differed in their resistance profiles. Most (97.2%) of them were resistant to at least one of the drugs tested, but only 25.4% showed a multidrug resistance phenotype. The highest resistance rate was observed for lincomycin (93%), followed by tetracycline (85.9%). This study confirmed a low prevalence of β-lactam resistance in Strep. uberis, with only one isolate showing resistance to six antimicrobial classes, including cephalosporins.